The Efficiency Cassava Marketing in Lohia District, Muna Regency - Cindy Mentari; Surni; Rosmawaty (International journal of technology and education research, 2026)
This study aims to (1) identify the marketing channels of cassava in Lohia District, Muna Regency, and (2) determine the efficiency and marketing margin of cassava in Lohia District, Muna Regency. The research was conducted in Lohia District, Muna Regency, from November 2024 to March 2025. The study employed descriptive analysis, marketing margin analysis, and marketing efficiency analysis (Farmer's Share). The respondents consisted of 30 cassava farmers selected using simple random sampling, and 6 retailers selected using snowball sampling. The results of the study indicate that: (1) there are two marketing channels, namely: (a) Farmer–Consumer and (b) Farmer–Retailer–Consumer; (2) the marketing margin obtained in Channel II was IDR 6,000 per kilogram. The analysis of the percentage of the price received by farmers (farmer's share) in Channel II was 54%, which demonstrates that cassava marketing in Lohia District operates efficiently.